The Effects of Fire in Human Life and in the Cuisine from the Paleolithic to the Modern Age - Badem, Abdullah (Journal of Ecohumanism, 2024)
Humans existed on earth 2.5 million years ago and took control of fire after their evolutionary transformations. As a result of consuming cooked meat, there was an increase in the size of the human brain, the use of hands and mental skills. With the beginning of the Neolithic period, the increasing bio-cultural and socio-cultural transformation of humans also affected food preparation, storage and kitchen tools. People started to produce to prepare and consume food, hunt animals and facilitate agriculture. In the past, in addition to frying meat, they found different cooking methods using tools such as fire pits, clay balls and earthenware. The food processing and preservation methods developed and widely used from the Paleolithic period to the Neolithic period are cooking, grinding, drying, salting, seasoning, cheese-yoghurt, oil/sugar storage and fermentation processes, which are explained in detail in the article. As a result of the research, it was seen that all of these methods interacted with fire (and heat) to a greater or lesser extent. The (basic) cooking methods of food include (dry heat) frying, roasting, smoking (smoking), (wet heat) boiling, simmering and perhaps steaming. Changes in human eating habits appear to affect body size, digestion and health conditions.